Establishment of Reference Norms for Lung Function Parameters of Healthy Sri Lankan Tamils - Sooriyakanthan, Mathanki; Wimalasekera, Savithri; Kanagasabai, Sivapalan (Pulmonary Medicine, 2019)
Spirometry and Peak Expiratory Flow Rate (PEFR) are important measurements in diagnosing and monitoring of COPD and asthma. Ethnic specific reference equations are necessary in interpretation of these parameters. However, equations for Sri Lankan Tamil adults are not available. This study aims to establish reference equations for lung function parameters of Sri Lankan Tamils. A descriptive cross sectional study was carried out in all 5 districts of Northern Sri Lanka. Participants were selected by cluster sampling. Base line data were obtained by a questionnaire. Height, sitting height, weight, arm span, mid arm circumference, and chest expansion were measured. Respiratory functions were assessed by a calibrated spirometer (Cosmed Micro Quark, Italy) and Wright compatible peak expiratory flow meter. Means, and standard deviations for Vital Capacity (VC), Forced Vital Capacity (FVC), Forced Expiratory Volume in the first second (FEV1), FEV1%, Peak Expiratory Flow Rate (PEFR) and for other forced expiratory parameters of 775 males and 687 females were determined. Lung function parameters have significant p<0.05 positive correlations with most of the anthropometric measures. Age had a significant p<0.05 negative correlation with lung function parameters in adults >20 years and positive correlation p<0.05 in 14–20 years group. Step wise multiple regression analysis was used to determine the prediction equations. Also equations based on age, height and age, arm span were derived. Age, height based equations were retested in the same population. Predicted values by the developed equations had better agreement than that of GLI 2012 equations. This can be useful in assessing the respiratory function in Sri Lankan Tamil population as there are no already existing equations.